Promoting a Healthy Lifestyle through the Cigarette Smoke-Free Home Movement - Ahmad Syauqi Hidayatullah; Anselmus Sudirman; Johanes Climacus Setyo Karjono; Sulistyo Budiarto; Petrus Piro Bani; Lita Indah Sari; Maria Advenia Wango (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Smoking and secondhand exposure provide significant health and economic issues in environments where indoor smoking is prevalent. This Community Service-Oriented (PkM) research aims to: 1) identify the level of knowledge, attitudes, and commitment in Dusun Ngargosoko Wetan concerning smoking hazards before and after the implementation of a cigarette smoke-free home PkM program; and 2) investigate how the initiative can enhance family health, fortify socio-religious cohesion, and alleviate economic burdens in low-income households. This community service-oriented research utilized a defined Participatory Action Research (PAR) cycle (planning → action → reflection → revision) to collaboratively create and implement a full-day intervention for 40 intentionally selected residents (25 adult men, predominantly fathers/young adults, 15 adolescents). The majority of participating homes had children and reported low to moderate incomes. Pre/post questionnaires assessed knowledge, attitudes, and household regulations; enabled small-group conversations incorporating socio-religious messages and generated family commitments. Quantitative analyses (SPSS v26; R v4.2) employed paired t-tests for continuous variables. A community-led three-month follow-up was scheduled to evaluate enduring change. The results indicate that the average knowledge improved from 62.5 to 81.3, reflecting a 30% relative improvement (paired t-test, p < .01). Post-event commitments: 65% embraced smoke-free household promises, 25% aimed to decrease smoking, 10% remained unchanged. The implementation of PAR cycles and socio-religious framing yielded immediate, substantial benefits and created local monitoring systems to facilitate long-term sustainability and policy adoption.